Residuos, Degradación y Persistencia del Fungicida Maneb en Patatas en Costa Rica - Diez Martin, Vera (1983)
Residues of the fungicide maneb (manganese-1,2-ethylen-bisdithiocarbamate) were analyzed by the carbondisulfide evolution method in samples of potatoes, potato leaves and soil from a commercial crop located in Llano Grande de Cartago, Costa Rica. The residues were monitored during all the crop until harvesting. The highest amount in the potato tubers was 0.25 ppm. In the soil the maximum residues found was 14 ppm and the minimum was 0.8 ppm. The corresponding values in the leaf samples were 492 ppm and 22 ppm respectively The degradation of maneb in the soil (sandy-loam type) under outdoor conditions showed pseudo-first-order kinetics with a half-life of 10.6 days. A similar study of the degradation of the pesticide in the potato tubers resulted in a half-life of maneb of only 5.2 hours. After photochemical irradiation of maneb suspended in water and in the absence of oxygen, carbon disulfide and ethylenediamine were determined as decomposition products. All maneb disappeared within 1 h irradiation. Recovery values for residues of maneb are in the order of 82-99%.